KHITAN WANITA PERSPEKTIF MEDIS DAN HUKUM ISLAM - Ibnu Amin (UIN Imam Bonjol Padang, 2022)
The term circumcision is not found in the Quran (both as ibarah al-nash and isyarat al-nash) moreover it means the verse to legalize female circumcision. The verse that is often quoted by some scholars to back up the practice of circumcision is the letter an-Nisa' verse 125, surah: 125 and Ali Imran, verse: 95, namely the recommendation to follow Ibrahim's millah, one of the millahs is circumcision. Medical research concluded that female circumcision is not a medical procedure because its implementation is not based on medical indications and has not proven its benefits to the health of the woman as stated in the consideration of Minister of Health Regulation No. 6/2014 concerning Revocation of Minister of Health Regulation 1636/2010 concerning Female Circumcision. Tracing the history that female circumcision departs from the legacy of the Arab tradition that has lasted a long time and when the arrival of Islam got the legitimacy of the Prophet that female circumcision is a